ANALISIS PENGARUH PROMOSI USAHA PONDOK LAUNDRY DI MAKASSAR TERHADAP PENJUALAN MENGGUNAKAN METODE UJI ANALISIS REGRESI SEDERHANA - Ratih Suwanti (Universitas Ichsan Sidenreng Rappang, 2025)
This research aims to determine the effect of promotion on sales volume at Pondok Laundry, Makassar, using a simple linear regression analysis method. The data used is primary data from 2025, covering sales and promotion activities. The analysis was performed using SPSS version 25.0. The results of the study show a regression equation of Y = 22,297 + 2,468X. The statistical tests indicate that promotion has a positive and significant effect on sales. This is evidenced by the regression coefficient of 2.468, which means every one-unit increase in promotion results in an increase in sales by 2.468 units. Therefore, the implementation of effective promotional strategies is highly recommended for business owners to optimize turnover and maintain business continuity in a competitive market.